The treatment of pediatric chronic myelogenous leukemia in the imatinib era - Jae Wook Lee; Nack Gyun Chung (Korean Pediatric Society, 2011)
Childhood chronic myelogenous leukemia (CML) is a rare hematologic disease, with limited literature on the methods of treatment. Previously, allogeneic hematopoietic stem cell transplantation (HSCT) was considered the only curative treatment for this disease. Treatment with imatinib, a selective inhibitor of the BCR-ABL tyrosine kinase (TKI), has resulted in prolonged molecular response with limited drug toxicity. Imatinib is now implemented in the primary treatment regimen for children, but the paucity of evidence on its ability to result in permanent cure and the potential complications that may arise from long-term treatment with TKIs have prevented imatinib from superseding HSCT as the primary means of curative treatment in children. The results of allogeneic HSCT in children with CML are similar to those observed in adults; HSCT-related complications such as transplant-related mortality and graft-versus-host disease remain significant challenges. An overall consensus has been formed with regards to the need for HSCT in patients with imatinib resistance or those with advanced-phase disease. However, issues such as when to undertake HSCT in chronic-phase CML patients or how best to treat patients who have relapsed after HSCT are still controversial. The imatinib era calls for a reevaluation of the role of HSCT in the treatment of CML. Specific guidelines for the treatment of pediatric CML have not yet been formulated, underscoring the importance of prospective studies on issues such as duration of imatinib treatment, optimal timing of HSCT and the type of conditioning utilized, possible treatment pre- and post-HSCT, and the role of second-generation TKIs.